Զաքարյանների և Օրբելյանների փոխհարաբերությունների պատմության շուրջ - Շահնազարյան, Արտաշես Ի. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The relationship between the Zakarians and Orbelians began in 1118 or shortly thereafter and lasted until 1289/1290. In the beginning, the Zakarians were the loyal subordinates of the Orbelis, the direct ancestors of the Orbelis. However, in 1176-1177, during the rebellion led by Ivane Orbeli against the Georgian king George III, they left the Orbelis and went over to the king's side. Отношения между Закарянами и Орбелянами начались в 1118 году, либо вскоре после этого и продолжались до 1289/1290 гг. Сначала Закаряны были верными вассалами Орбели, прямых предков Орбелянов. Однако во время мятежа, поднятого в 1176–1177 гг. против грузинского царя Георгия III под руководством Иване Орбели, Закаряны покинули Орбели и перешли на сторону короля.
Keywords: Հին պատմություն